Of Lady-killers and ‘Men Dressed As Women’: Soap Opera, Scapegoats and the Mexico City Police Department - Vek Lewis (PORTAL: Journal of Multidisciplinary International Studies, 2008)
Over two days in October 2005, police in Mexico City conducted a series of raids on male-to-female transgender (travesti) prostitutes working in the streets. The motive of the investigation was not related to sex work at all, but rather, the hunt for a serial killer responsible for the deaths of elderly women between 2003 and 2005. With few leads apart from reports by a couple of eyewitnesses that they had seen ‘a man dressed as a woman’ enter the houses of the victims, the Chief Public Prosecutor announced that the killer could be a travesti.